Latent failures on biodiesel plants - Rivera, Selva S. (2013)
The process to obtain biodiesel is simple, however it is a chemical process in which toxic and flammable substances are used or variables like temperature or pressure should be controlled to avoid any kind of incident. Literature report accidents where most human errors are related to the confidence of operators by this simplicity. Much of these accidents are influenced by a number of factors involved constituting latent failures. This paper presents a summary of latent failures identified on biodiesel plants and a description of their causes and the accepted practices to eliminate them.